2020
DOI: 10.2147/ijn.s233766
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hepatitis C Virus NS3 Protease and Helicase Inhibitors from Red Sea Sponge (<em>Amphimedon</em>) Species in Green Synthesized Silver Nanoparticles Assisted by in Silico Modeling and Metabolic Profiling</p>

Abstract: Background: Hepatitis C virus (HCV) infection is a major cause of hepatic diseases all over the world. This necessitates the need to discover novel anti-HCV drugs to overcome emerging drug resistance and liver complications. Purpose: Total extract and petroleum ether fraction of the marine sponge (Amphimedon spp.) were used for silver nanoparticle (SNP) synthesis to explore their HCV NS3 helicaseand protease-inhibitory potential. Methods: Characterization of the prepared SNPs was carried out with ultraviolet-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…The petroleum ether fraction was first chromatographed on a silica-gel column, and was then subjected to a sephadex LH-20 column and final purification on semi-preparative HPLC, yielding compounds 1 – 14 . These 14 compounds, as shown in Figure 1 , were identified based on their HR-ESIMS and by comparison with the literature, as nakinadine B ( 1 ), ircinol A ( 2 ), 6-hydroxymanzamine A ( 3 ), 3,4-dihydromanzamine A, J N-oxide ( 4 ), manzamine D ( 5 ), 3,4-dihydro-6-hydroxymanzamine A ( 6 ), pyrinodemin D ( 7 ), 7-methyl-6-hexadecenoic acid ( 8 ), methyl 2-methoxyhexadecanoate ( 9 ), 11,15-icosadienoicacid ( 10 ), 20-hepacosenoic acid ( 11 ), amphimedoside C ( 12 ), keramaphidin B ( 13 ), and amphimedine ( 14 ) [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The petroleum ether fraction was first chromatographed on a silica-gel column, and was then subjected to a sephadex LH-20 column and final purification on semi-preparative HPLC, yielding compounds 1 – 14 . These 14 compounds, as shown in Figure 1 , were identified based on their HR-ESIMS and by comparison with the literature, as nakinadine B ( 1 ), ircinol A ( 2 ), 6-hydroxymanzamine A ( 3 ), 3,4-dihydromanzamine A, J N-oxide ( 4 ), manzamine D ( 5 ), 3,4-dihydro-6-hydroxymanzamine A ( 6 ), pyrinodemin D ( 7 ), 7-methyl-6-hexadecenoic acid ( 8 ), methyl 2-methoxyhexadecanoate ( 9 ), 11,15-icosadienoicacid ( 10 ), 20-hepacosenoic acid ( 11 ), amphimedoside C ( 12 ), keramaphidin B ( 13 ), and amphimedine ( 14 ) [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…We previously studied the antiviral potential of Amphimedon sp., and our results indicated that Amphimedon sp. total extract and petroleum ether fractions, as well as their derived nanoparticles, had anti-HCV potential, with pyrinodemin D, nakinadine B, and 3,4-dihydro-6-hydroxymanzamine A being the most potent anti-HCV agents [ 16 ]. This prompted us to study the ability of isolated compounds to act as inhibitors of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in silico prediction studies of physicochemical properties, ADMET and drug-likeness parameters are utilized for the identification of the most promising leads. Herein, SwissADME software was employed to compute the physicochemical properties formulating drug-likeness parameters of the hit phytochemicals ( Table 2 ) [ 18 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the silver nanoparticle directly binds with the viral genome, disrupts their structure, and halts their proliferation in the host body [ 217 ]. Notably, the biogenic synthesized silver nanoparticle follows the same mechanism when a virus infects a host cell [ 218 ]. However, the chemical-based functional group in the AgNPs fabricated via physical or chemical approach can be toxic towards the infected host cell [ 219 ].…”
Section: Mechanism Of Antiviral Activity Of Agnps and Nanocomposites: Synthesis Perspectivementioning
confidence: 99%